Mating of natural Saccharomyces cerevisiae strains for improved glucose fermentation and lignocellulosic inhibitor tolerance - Jansen, Trudy; Hoff, Justin Wallace; Jolly, Neil; van Zyl, Willem Heber (Folia microbiologica, 2018)
Natural Saccharomyces cerevisiae isolates from vineyards in the Western Cape, South Africa were evaluated for ethanol production in industrial conditions associated with the production of second-generation biofuels. The strains displayed high phenotypic diversity including the ability to grow at 45 °C and in the presence of 20% (v/v) ethanol, strain YI13. Strains HR4 and YI30 were inhibitor-tolerant under aerobic and oxygen-limited conditions, respectively. Spore-to-spore hybridization generated progeny that displayed heterosis, including increased ethanol productivity and improved growth in the presence of a synthetic inhibitor cocktail. Hybrid strains HR4/YI30#6 and V3/YI30#6 were able to grow at a high salt concentration (2 mol/L NaCl) with V3/YI30#6 also able to grow at a high temperature (45 °C). Strains HR4/YI30#1 and #3 were inhibitor-tolerant, with strain HR4/YI30#3 having similar productivity (0.36 ± 0.0036 g/L per h) as the superior parental strain, YI30 (0.35 ± 0.0058 g/L per h). This study indicates that natural S. cerevisiae strains display phenotypic variation and heterosis can be achieved through spore-to-spore hybridization. Several of the phenotypes (temperature-, osmo-, and inhibitor tolerance) displayed by both the natural strains and the generated progeny were at the maximum conditions reported for S. cerevisiae strains.
Keywords: Saccharomyces cerevisiae; lignin; fungální geny pro párovací typ; Lignin; Fermentation; ethanol; fermentace; Jihoafrická republika; Ethanol; Genes, Mating Type, Fungal; Hot Temperature; South Africa; Glucose; vysoká teplota; glukosa